Application of Modified Vigenere Cipher Cryptography Technique in Text Data Encryption in Web Based Applications - Romanus Damanik; Hardiman Ruhut M. Simamora; Bersama Sinuraya; Pardede, A M H (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of information technology in today's digital era has brought rapid progress, especially in terms of data security which is a major concern in various sectors. In securing data or information, the application of cryptographic techniques is becoming increasingly important. The vigenere cipher algorithm is one of the classic cryptographic methods widely used for text encryption. However, the standard form of encryption algorithm has weaknesses, especially in terms of its vulnerability to frequency analysis attacks that can be used to break the encryption pattern if the key used is repeated. This research aims to design and implement a modified Vigenere cipher on a web-based application to improve encryption security. The designed web-based application is a password manager that is used as a test to show what the application of the vigenere cipher modification looks like in an application. The password manager application designed has the features of registering, logging in, storing, managing, and securing various passwords and login information for websites, applications, or online services. sensitive data in this application such as login information is encrypted before being stored in the database and decrypted when displayed to the user.This implementation is expected to show the application of the Vigenere Cipher modification in securing data in web-based applications.